The Cosmetics Industry in Romania: Analysis of Economic Performance and Trends - Carmen- Cristina Runceanu-Albu (Ovidius University Annals: Economic Sciences Series, 2025)
The cosmetics and personal care products industry have shown an upward trend recently, both globally and in Romania. The need for analysis of Romania's cosmetics sector is justified by highlighting socio-economic aspects due to changes in consumer behavior. In this context, the research involves analyzing statistical data on cosmetics manufacturing organizations in Romania, estimating consumption trends, and tracking the evolution of these organizations. The analysis shows that key indicators such as the number of manufacturers, turnover, and number of employees in Romania’s cosmetics industry have increased. These values provide an overview of the sector's vitality, reflecting connections to changes in consumer habits.